Gender differences in optimism - Carl Magnus Bjuggren; Niklas Elert (Research Institute of Industrial Economics (IFN), 2019)
This paper examines gender differences in optimism about the economy. We measure optimism using Swedish survey data in which respondents stated their beliefs about the country's future economic situation. We argue that this measure of optimism is preferable to common measurements in the literature since it avoids confounding individuals' economic situation with their perception of the future and it can be compared to economic indicators. In line with previous research, we find that men are more optimistic than women; however, men are also more prone to be wrong in their beliefs about the future economic situation. Furthermore, in sharp economic downturns, the gender differences in optimism disappear. This convergence in beliefs can be explained by the amount of available information on the economy.
Keywords: J16; D83; 330; Gender; Optimism; Perception of the future; Economic downturns